Increased Polyamines Alter Chromatin and Stabilize Autoantigens in Autoimmune Diseases - Brooks, Wesley H. (Frontiers in Immunology, 2013)
Polyamines are small cations with unique combinations of charge and length that give them many putative interactions in cells. Polyamines are essential since they are involved in replication, transcription, translation, and stabilization of macro-molecular complexes. However, polyamine synthesis competes with cellular methylation for S-adenosylmethionine, the methyl donor. Also, polyamine degradation can generate reactive molecules like acrolein. Therefore, polyamine levels are tightly controlled. This control may be compromised in autoimmune diseases since elevated polyamine levels are seen in autoimmune diseases. Here a hypothesis is presented explaining how polyamines can stabilize autoantigens. In addition, the hypothesis explains how polyamines can inappropriately activate enzymes involved in NETosis, a process in which chromatin is modified and extruded from cells as extracellular traps that bind pathogens during an immune response. This polyamine-induced enzymatic activity can lead to an increase in NETosis resulting in release of autoantigenic material and tissue damage.